Comparative assessment of microsatellite and RAPD markers and their efficiency in DNA fingerprinting of upland cotton (Gossypium hirsutum) - WAGHMARE, VIJAY N; SUTAR, S R; THAKRE, P B; SAPKAL, D R; SALAME, R V; BADOLE, A M; PATIL, B R (The Indian Journal of Agricultural Sciences, 2026)
A statistical approach was employed to compare the potential of microsatellite (SSR) and RAPD markers for identification, diversity analysis and genotype discrimination. Twentyfour SSR and seventeen RAPD primers were screened across 91 upland cotton (50 maintainer and 41 restorers) accessions. Major parameters, i e polymorphism information content (PIC), resolving power (Rp) and marker index (MI), were computed and compared for their ability to discriminate among the accessions. PIC, Rp and MI values displayed wide variation among SSR and RAPD markers. MI values showed excellent linear relationship with number of genotypes identified (r2 = 0.70 and 0.69) by SSR and RAPD markers than Rp (r2= 0.63, 0.56). SSR and RAPD markers selected based on informative PIC, high Rp and MI values independently discriminate majority of accessions. However, combined use of SSR and RAPD markers, increases the efficiency and discrimination power. Minimum of 8 markers (4 SSR and 4 RAPD) possessing high MI and Rp values were found to discriminate as many as 90 out of 91 accessions. This study reveals that selection of markers based on Rp and MI values for DNA fingerprinting and diversity studies was highly reliable and such selective markers could be effectively used for characterization of large germplasm accessions.